Clinicopathologic Features of Carcinoma of the Cervix Uteri at Prof. Dr. I.G.N.G. Ngoerah Hospital in 2021-2022 - Paramitha, Ni Made Laksmi Dewi; Dewi, I Gusti Ayu Sri Mahendra; Paskarani, Putu Erika; Winarti, Ni Wayan (http://dharmais.co.id/, 2025)
Background: Cervical cancer is a malignant tumor of the cervix with a high mortality rate, primarily identified by vaginal bleeding. Human papillomavirus (HPV) infection was found in 99.7% of cervical cancer cases. Other risk factors include age at first sexual intercourse, parity, smoking, weak immune system, use of oral contraceptives, and a high number of sexual partners. This study aims to analyze and describe the clinicopathological features of cervical carcinoma, including patient demographics, primary symptoms, histopathological types, and tumor staging, at Prof. Dr. I.G.N.G. Ngoerah Hospital from 2021 to 2022.Method: This study employs a descriptive research method with a retrospective approach, utilizing secondary data and comprising 283 samples. Inclusion criteria included patients diagnosed with cervical carcinoma confirmed by histopathological evaluation and complete medical records documenting age, primary complaints, histopathological classification, and TNM staging. Data were processed and presented using descriptive statistics. Results: The results showed that the age group with the highest number of cervical carcinoma cases was the 40-49 years age group (36.0%), the most common main complaint was bleeding (68.9%), the most common histopathological type was squamous cell carcinoma (78.8%), and the most common TNM stage was T1 (52 cases) and N0 (87 cases).Conclusion: This study highlights that cervical carcinoma predominantly affects women aged 40–49 years, with abnormal vaginal bleeding as the most common symptom. Squamous cell carcinoma was the most common histopathological type (78.8%), with the majority of cases staged at T1 (18.4%) and N0 (30.7%).